The 'beautiful' in information: thoughts about visual literacy and aesthetics. Issue 1 (2nd January 2016) - Benoît, Gerald
Abstract: Many agencies have promulgated standards for visual literacy. These groups include libraries, museums, computer science and graphic designers. The implementation of these standards tends to be skill-based courses for production. Other, larger questions about visual literacy are eclipsed and the growing number of research areas investigating visual literacy has made a complicated, contradictory literature. The dominant stream of discourse in the humanities emphasizes cultural, historical and social-constructionist perspectives. An alternative perspective, which was dominant until the 1970s, still seems to lead the sciences, a pseudo-objectivist perspective. The theme of this essay is that considering visual literacy from a yet-earlier analysis, that of Immanuel Kant's Critique of judgment about 'beauty, ' may lead to a shareable discourse to advance our study about the interpretation of visuals and create a foundation to allow for individual and community-based interpretations, a middle-way between an entirely strict empiricist view and a hyper-relative socially constructed one. This approach may be controversial, but all the more useful to sparking discussion of deeper issues about interpretation and professionals' advancement in visual literacy.